ANTI-WHIPPING SIMULATION OF HIGH ENERGY PIPE IN NUCLEAR POWER PLANT BASED ON THE Ω-SHAPE ANTI WHIPPING RESTRAINT - ZHENG JinPing; WU JiYe; XUE MeiXin; SONG LinHui (Jixie qiangdu)
Based on ABAQUS,the process of the high-energy pipeline rejection and anti-whipping performance of the Ω-shape anti-whipping restraints of the nuclear power plant are simulated and analyzed. By analyzing of the deformation and failure process of common U-shaped anti-whipping restraints,the Ω-shape anti-whipping restraint is proposed to replace U-shaped antiwhipping restraints and the specific geometric dimensions of the Ω-shape anti-whipping restraint are given. The model of pipe-Ω-shape anti-whipping restraints system is established,and its whipping process is analyzed by FEM software ABAQUS,which discloses that the Ω-shape anti-whipping restraint is able to remarkably reduce the stress peak and the maximum whipping force of the pipe--anti-whipping restraints system,thus improve the safety of the high-energy pipe system.